Tidepools, Pacific Grove with Hopkins Lab in Background - Richard L. Allman:::Creator:::::::::::: (Monterey, California; U.S.A.)
Pacifc Grove tidepools, looking toward Cabrillo Point with the Hopkins Marine Station in the background. RESTRICTED USE